PLAGIARISM AND ITS IMPACTS ON TEACHING PRACTICES: INSIGHTS FROM THE INDONESIAN LECTURERS - Risa Fitria; Disa Evawani Lestari; Ani Pujiastuti; Grace Amialia Anfetonanda; Maria Yus Trinity Irsan (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This paper discusses the EFL lecturers’ views on plagiarism following their exposure to two distinct educational environments, their home university and Western universities. While existing literature has examined lecturers' views on plagiarism, there is a scarcity of research specifically investigating the perceptions of Western graduate lecturers and the influence of these perspectives on their pedagogical approaches. The present study aimed to address two research inquiries: 1) How did Indonesian EFL lecturers' opinions on plagiarism evolve between two academic communities over time? 2) What were the impact of the participants’ shifting views on their existing educational practice? The research employed semi-structured interviews as the primary method for data collection. Data were collected through interviews with a sample of nine EFL lecturers affiliated with a state academic institution in Indonesia. The findings indicated that the lecturers' views on plagiarism have undergone a shift due to their experiences studying abroad. This study suggests that the participants’ views has been shaped not only by the Western culture, but also by their own cultural backgrounds, such as religious beliefs. In terms of pedagogical practice, educators have transferred their understanding of plagiarism to their students by implementing their preferred pedagogical practice as well as consequences of plagiarism. This study highlights the need for Indonesian educators and policymakers to adapt Western perspectives on plagiarism to the Indonesian context. The adoption of Western perspectives may not align with the current academic context, highlighting the need for reform in pedagogical practice and cultural awareness. Policymakers should reassess the current approach to plagiarism prevention and consider adaptation within the Indonesian context.